2016
DOI: 10.1007/s00247-016-3736-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced magnetic resonance imaging of the wrist in children with juvenile idiopathic arthritis

Abstract: BackgroundDynamic contrast-enhanced MRI provides information on the heterogeneity of the synovium, the primary target of disease in children with juvenile idiopathic arthritis (JIA).ObjectiveTo evaluate the feasibility of dynamic contrast-enhanced MRI in the wrist of children with JIA using conventional descriptive measures and time-intensity-curve shape analysis. To explore the association between enhancement characteristics and clinical disease status.Materials and methodsThirty-two children with JIA and wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…9 In children with JIA, DCE-MRI was found to be a valuable tool for detecting synovitis, including in the temporomandibular joint. 34,35 Diffusion Weighted Imaging (DWI) has been successfully applied in inflammatory rheumatic diseases. 36 It has been shown that apparent diffusion coefficient (ADC) discriminates between active and inactive JIA, and identifies patients with AS, nonradiographic AS, and lower back pain not due to AS at baseline.…”
Section: Update In Magnetic Resonance Imagingmentioning
confidence: 99%
“…9 In children with JIA, DCE-MRI was found to be a valuable tool for detecting synovitis, including in the temporomandibular joint. 34,35 Diffusion Weighted Imaging (DWI) has been successfully applied in inflammatory rheumatic diseases. 36 It has been shown that apparent diffusion coefficient (ADC) discriminates between active and inactive JIA, and identifies patients with AS, nonradiographic AS, and lower back pain not due to AS at baseline.…”
Section: Update In Magnetic Resonance Imagingmentioning
confidence: 99%
“…DCE-MRI proved to be a feasible technique in children with active arthritis in wrists, hips and knee joints. 8,[26][27][28] In JIA, DCE-MRI showed to be able to differentiate children with active and inactive JIA by the differences in the relative number of TIC shapes (TIC shape type 4, ►Fig. 1) as well as with descriptive parameters of maximum enhancement, maximal initial slope and the initial area under the curve.…”
Section: Dce-mri In Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…1) as well as with descriptive parameters of maximum enhancement, maximal initial slope and the initial area under the curve. 8,28 Workie et al, showed that DCE-MRI was sensitive to change since a decrease in pharmacokinetic parameter values corresponded with reduction of disease activity. 27 Regarding the construct validity of DCE-MRI in JIA, DCE parameters correlated in JIA patients moderately to substantially with conventional Juvenile Arthritis MRI Scores (JAMRIS) of disease activity in children with knee involvement.…”
Section: Dce-mri In Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Finally, DCE-MRI has been proposed as a potential biomarker in children with juvenile idiopathic arthritis and wrist involvement demonstrating an association between clinical active disease and derived-parameters such as maximum relative enhancement[ 56 ].…”
Section: Clinical Scenariosmentioning
confidence: 99%